Respuesta :
Answer:
The solution is too long. So, I included them in the explanation
Step-by-step explanation:
This question has missing details. However, I've corrected each question before solving them
Required: Determine the inverse
1:
[tex]f(x) = 25x - 18[/tex]
Replace f(x) with y
[tex]y = 25x - 18[/tex]
Swap y & x
[tex]x = 25y - 18[/tex]
[tex]x + 18 = 25y - 18 + 18[/tex]
[tex]x + 18 = 25y[/tex]
Divide through by 25
[tex]\frac{x + 18}{25} = y[/tex]
[tex]y = \frac{x + 18}{25}[/tex]
Replace y with f'(x)
[tex]f'(x) = \frac{x + 18}{25}[/tex]
2. [tex]g(x) = \frac{12x - 1}{7}[/tex]
Replace g(x) with y
[tex]y = \frac{12x - 1}{7}[/tex]
Swap y & x
[tex]x = \frac{12y - 1}{7}[/tex]
[tex]7x = 12y - 1[/tex]
Add 1 to both sides
[tex]7x +1 = 12y - 1 + 1[/tex]
[tex]7x +1 = 12y[/tex]
Make y the subject
[tex]y = \frac{7x + 1}{12}[/tex]
[tex]g'(x) = \frac{7x + 1}{12}[/tex]
3: [tex]h(x) = -\frac{9x}{4} - \frac{1}{3}[/tex]
Replace h(x) with y
[tex]y = -\frac{9x}{4} - \frac{1}{3}[/tex]
Swap y & x
[tex]x = -\frac{9y}{4} - \frac{1}{3}[/tex]
Add [tex]\frac{1}{3}[/tex] to both sides
[tex]x + \frac{1}{3}= -\frac{9y}{4} - \frac{1}{3} + \frac{1}{3}[/tex]
[tex]x + \frac{1}{3}= -\frac{9y}{4}[/tex]
Multiply through by -4
[tex]-4(x + \frac{1}{3})= -4(-\frac{9y}{4})[/tex]
[tex]-4x - \frac{4}{3}= 9y[/tex]
Divide through by 9
[tex](-4x - \frac{4}{3})/9= y[/tex]
[tex]-4x * \frac{1}{9} - \frac{4}{3} * \frac{1}{9} = y[/tex]
[tex]\frac{-4x}{9} - \frac{4}{27}= y[/tex]
[tex]y = \frac{-4x}{9} - \frac{4}{27}[/tex]
[tex]h'(x) = \frac{-4x}{9} - \frac{4}{27}[/tex]
4:
[tex]f(x) = x^9[/tex]
Replace f(x) with y
[tex]y = x^9[/tex]
Swap y with x
[tex]x = y^9[/tex]
Take 9th root
[tex]x^{\frac{1}{9}} = y[/tex]
[tex]y = x^{\frac{1}{9}}[/tex]
Replace y with f'(x)
[tex]f'(x) = x^{\frac{1}{9}}[/tex]
5:
[tex]f(a) = a^3 + 8[/tex]
Replace f(a) with y
[tex]y = a^3 + 8[/tex]
Swap a with y
[tex]a = y^3 + 8[/tex]
Subtract 8
[tex]a - 8 = y^3 + 8 - 8[/tex]
[tex]a - 8 = y^3[/tex]
Take cube root
[tex]\sqrt[3]{a-8} = y[/tex]
[tex]y = \sqrt[3]{a-8}[/tex]
Replace y with f'(a)
[tex]f'(a) = \sqrt[3]{a-8}[/tex]
6:
[tex]g(a) = a^2 + 8a- 7[/tex]
Replace g(a) with y
[tex]y = a^2 + 8a - 7[/tex]
Swap positions of y and a
[tex]a = y^2 + 8y - 7[/tex]
[tex]y^2 + 8y - 7 - a = 0[/tex]
Solve using quadratic formula:
[tex]y = \frac{-b\±\sqrt{b^2 - 4ac}}{2a}[/tex]
[tex]a = 1[/tex] ; [tex]b = 8[/tex]; [tex]c = -7 - a[/tex]
[tex]y = \frac{-b\±\sqrt{b^2 - 4ac}}{2a}[/tex] becomes
[tex]y = \frac{-8 \±\sqrt{8^2 - 4 * 1 * (-7-a)}}{2 * 1}[/tex]
[tex]y = \frac{-8 \±\sqrt{64 + 28 + 4a}}{2 * 1}[/tex]
[tex]y = \frac{-8 \±\sqrt{92 + 4a}}{2 * 1}[/tex]
[tex]y = \frac{-8 \±\sqrt{92 + 4a}}{2 }[/tex]
Factorize
[tex]y = \frac{-8 \±\sqrt{4(23 + a)}}{2 }[/tex]
[tex]y = \frac{-8 \±2\sqrt{(23 + a)}}{2 }[/tex]
[tex]y = -4 \±\sqrt{(23 + a)}[/tex]
[tex]g'(a) = -4 \±\sqrt{(23 + a)}[/tex]
7:
[tex]f(b) = (b + 6)(b - 2)[/tex]
Replace f(b) with y
[tex]y = (b + 6)(b - 2)[/tex]
Swap y and b
[tex]b = (y + 6)(y - 2)[/tex]
Open Brackets
[tex]b = y^2 + 6y - 2y - 12[/tex]
[tex]b = y^2 + 4y - 12[/tex]
[tex]y^2 + 4y - 12 - b = 0[/tex]
Solve using quadratic formula:
[tex]y = \frac{-b\±\sqrt{b^2 - 4ac}}{2a}[/tex]
[tex]a = 1[/tex] ; [tex]b = 4[/tex]; [tex]c = -12 - b[/tex]
[tex]y = \frac{-b\±\sqrt{b^2 - 4ac}}{2a}[/tex] becomes
[tex]y = \frac{-4\±\sqrt{4^2 - 4 * 1 * (-12-b)}}{2*1}[/tex]
[tex]y = \frac{-4\±\sqrt{4^2 - 4 *(-12-b)}}{2}[/tex]
Factorize:
[tex]y = \frac{-4\±\sqrt{4(4 - (-12-b))}}{2}[/tex]
[tex]y = \frac{-4\±2\sqrt{(4 - (-12-b))}}{2}[/tex]
[tex]y = \frac{-4\±2\sqrt{(4 +12+b)}}{2}[/tex]
[tex]y = \frac{-4\±2\sqrt{16+b}}{2}[/tex]
[tex]y = -2\±\sqrt{16+b}[/tex]
Replace y with f'(b)
[tex]f'(b) = -2\±\sqrt{16+b}[/tex]
8:
[tex]h(x) = \frac{2x+17}{3x+1}[/tex]
Replace h(x) with y
[tex]y = \frac{2x+17}{3x+1}[/tex]
Swap x and y
[tex]x = \frac{2y+17}{3y+1}[/tex]
Cross Multiply
[tex](3y + 1)x = 2y + 17[/tex]
[tex]3yx + x = 2y + 17[/tex]
Subtract x from both sides:
[tex]3yx + x -x= 2y + 17-x[/tex]
[tex]3yx = 2y + 17-x[/tex]
Subtract 2y from both sides
[tex]3yx-2y =17-x[/tex]
Factorize:
[tex]y(3x-2) =17-x[/tex]
Make y the subject
[tex]y = \frac{17 - x}{3x - 2}[/tex]
Replace y with h'(x)
[tex]h'(x) = \frac{17 - x}{3x - 2}[/tex]
9:
[tex]h(c) = \sqrt{2c + 2}[/tex]
Replace h(c) with y
[tex]y = \sqrt{2c + 2}[/tex]
Swap positions of y and c
[tex]c = \sqrt{2y + 2}[/tex]
Square both sides
[tex]c^2 = 2y + 2[/tex]
Subtract 2 from both sides
[tex]c^2 - 2= 2y[/tex]
Make y the subject
[tex]y = \frac{c^2 - 2}{2}[/tex]
[tex]h'(c) = \frac{c^2 - 2}{2}[/tex]
10:
[tex]f(x) = \frac{x + 10}{9x - 1}[/tex]
Replace f(x) with y
[tex]y = \frac{x + 10}{9x - 1}[/tex]
Swap positions of x and y
[tex]x = \frac{y + 10}{9y - 1}[/tex]
Cross Multiply
[tex]x(9y - 1) = y + 10[/tex]
[tex]9xy - x = y + 10[/tex]
Subtract y from both sides
[tex]9xy - y - x = y - y+ 10[/tex]
[tex]9xy - y - x = 10[/tex]
Add x to both sides
[tex]9xy - y - x + x= 10 + x[/tex]
[tex]9xy - y = 10 + x[/tex]
Factorize
[tex]y(9x - 1) = 10 + x[/tex]
Make y the subject
[tex]y = \frac{10 + x}{9x - 1}[/tex]
Replace y with f'(x)
[tex]f'(x) = \frac{10 + x}{9x -1}[/tex]